2011
DOI: 10.1017/s0022278x1100005x
|View full text |Cite
|
Sign up to set email alerts
|

Illiberal peacebuilding in Angola

Abstract: Angola's oil-fuelled reconstruction since the end of the civil war in 2002 is a world away from the mainstream liberal peacebuilding approach that Western donors have promoted and run since the end of cold war. The Angolan case is a pivotal example of what can be termed ‘illiberal peacebuilding’, a process of post-war reconstruction managed by local elites in defiance of liberal peace precepts on civil liberties, the rule of law, the expansion of economic freedoms and poverty alleviation, with a view to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 28 publications
0
23
0
4
Order By: Relevance
“…This leads to the case of the “illiberal state-building” of Angola, where the elite is invoking, among others, the lack of human resources to justify a different state-building “in defiance of liberal peace precepts on civil liberties, the rule of law, the expansion of economic freedoms and poverty alleviation” [ 44 ]. De Oliveira, in company with most historians and economists, is doubtful of the real commitment of predatory elites to human resource development.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the case of the “illiberal state-building” of Angola, where the elite is invoking, among others, the lack of human resources to justify a different state-building “in defiance of liberal peace precepts on civil liberties, the rule of law, the expansion of economic freedoms and poverty alleviation” [ 44 ]. De Oliveira, in company with most historians and economists, is doubtful of the real commitment of predatory elites to human resource development.…”
Section: Resultsmentioning
confidence: 99%
“…It is even difficult to argue that power takes the same form in such different (post-)conflict settings as Bosnia and Herzegovina, where the international community is seeking to (re)integrate a middle-income, formerly authoritarian state into Europe's 'core' from its 'periphery', establishing conditions for the abuse of public office though a lack of legitimacy, poorly designed political structures and economic liberalization efforts; 36 Afghanistan, where a highly militarized intervention influences and interacts with a decentralized conflict economy with regional dimensions in a weak state with high levels of poverty; 37 and Angola, where the state directs reconstruction efforts along lines that violate international orthodoxy. 38 Power, like resistance, takes many forms. It must be studied in its specific contexts and manifestations.…”
Section: The Role Of Powermentioning
confidence: 99%
“…Similarly, in Angola the MPLA (Movimento Popular de Libertação de Angola) won a convincing military victory in 2002 and firmly consolidated its domination. 46 This is not the case in countries where peacebuilding and state reconstruction issues are addressed together in the framework of peace negotiations. Jeremy Weinstein has shown that military victory tends to lead to more stable outcomes than negotiated settlement to conflict.…”
Section: The Developmental and The Illiberal Statementioning
confidence: 99%
“…While a return to conflict in Angola is not likely, there are normative tradeoffs in Angola's statebuilding project and limits to what is politically possible. 50 Illiberal statebuilding models thus do not offer a panacea to African countries emerging from conflict.…”
Section: The Developmental and The Illiberal Statementioning
confidence: 99%